Masticatory parameters of children with and without clinically diagnosed caries in permanent dentition - AKYÜZ, SERAP HATİCE (ARIESDUE SRL, 2017)
Aim Mastication turns food into a bolus and prepares it for chemical digestion. Any condition affecting tooth structure and position may have an impact on mastication. The aim of this study is to compare masticatory performance (MP) and maximum bite force (MBF) between children with and without clinically visible caries in permanent first molars. Materials and methods The study was conducted with 50 children in good general condition aged 12-14 years (25 girls, 25 boys) with no orthodontic/skeletal anomalies and no missing teeth due to dental trauma or extraction. Maximum bite force was measured bilaterally using strain gauge sensors. Masticatory performance was evaluated by silicone tablet comminution test. Results Masticatory performance was superior in caries-free children when compared to children with caries. Maximum bite force values in children with and without caries were not statistically different. Conclusions Caries reduces masticatory performance. Therefore, treatment is crucial for masticatory efficiency.
Keywords: Dental caries; Masticatory performance; Bite force; MAXIMUM BITE FORCE; DENTAL-CARIES; PRESCHOOL-CHILDREN; PERFORMANCE; ADULTS; BODY; OVERDENTURES; OCCLUSION; DENTURES